5LBS OF PRESSURE - Evans, Luke; Culkin, Rory; Adams, Zac; Pankow, Rudy (Lionsgate, 2026)
In this action-thriller, an ex-con back in his old neighborhood walking the path of forgiveness crosses destinies with an unhappy drug dealer, resulting in violence⁵ and redemption.